Method and estimation of parameters of dense part of double electrical layer at the interface electrode-solution of the dye in liquid crystal - Kovalchuk, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
First estimated were the parameters of dense part of double electrical layer (DEL) at the interface electrode – solution of the dye in liquid crystal, based on analysis of capacitance-voltage characteristics obtained at low frequencies, taking the series resistance into account. DELs with various parameters near each electrode were obtained owing to their different chemical compositions. It was shown that the obtained difference in the DEL parameters is caused not only by different chemical composition of the electrodes, but also different orientations of molecules near each of them (planar orientation near one electrode and homeotropic one near another). It was estimated the barrier height, thickness of near-electrode layer, and concentration of ionized states in the dense parts of DEL near each electrode. It was shown that these parameters differ by 2 to 3 times, and an assumption was made about the reasons that can cause this difference.